Advances in Proteomic Techniques for Cytokine Analysis: Focus on Melanoma Research - Kupcova Skalnikova, Helena; Cizkova, Jana; Cervenka, Jakub; Vodicka, Petr (International journal of molecular sciences, 2017)
Melanoma is a skin cancer with permanently increasing incidence and resistance to therapies in advanced stages. Reports of spontaneous regression and tumour infiltration with T-lymphocytes makes melanoma candidate for immunotherapies. Cytokines are key factors regulating immune response and intercellular communication in tumour microenvironment. Cytokines may be used in therapy of melanoma to modulate immune response. Cytokines also possess diagnostic and prognostic potential and cytokine production may reflect effects of immunotherapies. The purpose of this review is to give an overview of recent advances in proteomic techniques for the detection and quantification of cytokines in melanoma research. Approaches covered span from mass spectrometry to immunoassays for single molecule detection (ELISA, western blot), multiplex assays (chemiluminescent, bead-based (Luminex) and planar antibody arrays), ultrasensitive techniques (Singulex, Simoa, immuno-PCR, proximity ligation/extension assay, immunomagnetic reduction assay), to analyses of single cells producing cytokines (ELISpot, flow cytometry, mass cytometry and emerging techniques for single cell secretomics). Although this review is focused mainly on cancer and particularly melanoma, the discussed techniques are in general applicable to broad research field of biology and medicine, including stem cells, development, aging, immunology and intercellular communication.
Keywords: cancer; Tumor Microenvironment; imunoanalýza; secretome; nádorové mikroprostředí; proteomika; melanoma; Skin Neoplasms; Immunoassay; Melanoma; lidé; cytokiny; T-cell; Mass Spectrometry; Cytokines; ultrasensitive; biomarker; proteomics; Proteomics; cytokine; čipová analýza proteinů; melanom; imunoterapie; Humans; nádory kůže; Immunotherapy; mass spectrometry; hmotnostní spektrometrie; immunoassay; Protein Array Analysis